The beauty builder: a genealogical analysis of the production of female power and knowledge in artistic swimming - Yang, Y.; Hu, X. R.; Jiang, K. (International Review for the Sociology of Sport, 2025)
The study adopts a Foucauldian genealogical perspective to examine the transformation of gender discourse in artistic swimming. It highlights the importance of challenging the established gender norms and stereotypes in artistic swimming to promote greater gender inclusivity. By investigating archival documents and media coverages related to artistic swimming, the study unveils two discursive factors that result in the constitution of contemporary female-dominant discourse. First, male discourse has gradually diminished along with the development of the sport. Second, the continuous accumulation of female discourses concerning artistic swimming has produced genealogical knowledge aligned with female swimmers` physical and aesthetic traits. This knowledge ultimately contributes to the label of artistic swimming as a feminine sport and empowers women within its domain. The genealogical examination reveals the constructive nature and the production of the power/knowledge in artistic swimming and scrutinises the epistemological and historical antecedents of the prevalent stereotype surrounding the swimming pool.